Characterization of Plasma Activated Water Generated from Gliding Arc Discharge and Its Application on Enhancement of Seed Germination of Radish (Raphanus sativus var. longipinnatus) - Dhungana, Santosh; Guragain, Rajesh Prakash; Subedi, Deepak Prasad; Baniya, Hom Bahadur (Journal of Institute of Science and Technology, 2023)
In recent decades, generation of plasma activated water (PAW) from non-thermal atmospheric pressure plasma sources has received enormous attention due to their diverse applications. The research described in this paper is mainly focused on the preparation and characterisations of PAW produced from gliding arc discharge (GAD) operated with high voltages (9.7 kV, 50 Hz) power supply system and its use in the enhancement of seed germination of radish. The physical and chemical parameters of the PAW are investigated using a multi-parameter probe and UV-visible spectrometer. There are significant differences in physical parameters like pH and conductivity, and chemical parameters like concentration of nitrates, nitrites, ammonia in untreated and PAW. But no significant differences in temperature and total dissolved oxygen (TDO) are found. In order to determine the effects of PAW on seed germination, different germination parameters are calculated on radish (Raphanus sativus) which indicates that PAW can enhance the seed germination of radish.